Adsorption of Pb (II) Heavy Metals from Wastewater Using Modified Rice Husk as Adsorbent - Farid Mulana; Abrar Muslim; Pocut Nurul Alam; . Mariana (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2015)
Pb (II) heavy metal from wastewater as by-product of industrial activity often causes problem to environment. In order to minimize the amount of Pb (II), wastewater was treated in various ways, including adsorption process using adsorbent. Rice husks that containing lignin, cellulose, and hemicellulose are one of potential candidates to be utilized as adsorbent. The purpose of this research is to modify rice husk by using sodium hydroxide and citric acid and to know adsorption capacity and adsorption efficiency of modified rice husk adsorbent on Pb (II) metal uptake from wastewater. To identify substituted groups, analysis samples by using Fourier Transform Infrared was performed and to determine adsorbed amount of Pb (II) into adsorbent an Atomic Adsorption Spectroscopy Method was conducted. The result showed that optimum adsorption capacity and adsorption efficiency was 5.08 mg/g and 84.52%, respectively. These results were obtained on 60 ppm of Pb (II) adsorbate concentration and 0.8 M citric acid concentration for 150 minutes of contact time